Working Environment and Position to Employee Performance Improvement - Surakhmat; Ansar; Kurniawaty (Cendekiawan Indonesia Timur, 2023)
Work performance is the work achieved by a person in carrying out the tasks assigned to him based on skills, experience, sincerity, and time. A comfortable work environment, friendly and mutually supportive co-workers, and caring leaders will provide positive motivation at work. Employees will work for hand in hand with joy. Healthy competition in organizations or agencies. This study uses library research to examine the improvement of employee performance. The study results show that performance is what employees do, so it affects how much they contribute to the agency or organization, including the quality of services provided. Organizations in improving employee performance need the development of appropriate human resources with a supportive work environment. Factors used to enhance employee performance include individual abilities (knowledge, skills), the effort devoted, and organizational support. Employee performance is the result of the thought and energy of an employee on the work done, it can be tangible, seen, and counted in number, but in many cases, the results of thought and energy cannot be trusted and seen, such as ideas and innovations from employees to improve organizational progress.